Gestão autoritária e gestão democrática: suas caraterísticas e distinções - Santos, Jefferson Roberto de Carvalho (Universidade Federal de São Carlos, 2020)
This academic project talks about the aspects present in the conceptions we have of management work in contemporary society, mainly, with the objective of identifying and demonstrating the main characteristics and discussions between the authoritarian management model and the democratic management model inside of the schools, realizing its impact on everyone involved , the social effects on the school community, discussing the objectives that are proposed by each of these models of school organization, in addition to the influences that build them. The text develops from an analytical approach on neoliberalism and its influence on the authoritarian management model, bringing to the school surroundings strategies and ways of distributing work similar to those used in the business logic of making a profit. This logic of work only intensifies the authoritarianism imposed by the existing subjects in the school and destabilizes the fidelity of the school work to the main objective and social role of the school: to humanize the subjects through the access to the knowledge and culture accumulated historically by humanity, allowing the subjects see themselves in history and gain autonomy. The project aims to defend the impossibility of building a democratic management from neoliberalism and the impossibility of fulfilling the social objective of the school from an authoritarian management. As well as the constructed text and research points out that democratic management is the only way to organize the school community in a citizenship and with social quality. The conclusion was built based a documentary and data analysis of an opinion poll conducted with parents, teachers, staff and students on the establishment of a possible truly democratic management in the schools of the São Paulo State Education Network.
Authoritarian Management Model and The Democratic Management Model: Yours Characteristics and Distinctions
Keywords: gestão; democrática; neoliberalismo; autoritária; vitor paro; gestão escolar; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL